Attitude of Teachers Towards the Methods of Teaching English: A Study of Public Sector Schools in District Mardan (Journal of Asian Development Studies, 2025)
This paper examines the perception that teachers in the Tehsil Katlang, District Mardan, Pakistan, have towards various instructional techniques of teaching English in schools in the district, which falls under the public sector. The study focuses on determining the preferences of instructors regarding the methodology to teach, their views on existing practices, and their attitudes towards learning challenges in the classroom environment. A structured questionnaire, in the form of a Likert scale, was used to collect data from thirty teachers in four schools. The results of the survey indicate that most teachers prefer the Grammar-Translation Method (GTM). Still, many of them also use the Direct Method (DM) to help students develop their' better communication skills. Despite teachers having positive attitudes towards English language teaching, they face problems such as overcrowded classes, improper resources, outdated programs, and a lack of professional development opportunities. The paper concludes that teacher training, curriculum updates, and the provision of resources are vital to enhancing English teaching in state schools. These understandings emphasize policy changes and professional growth programs that enhance English language teaching in Pakistan.